Validation of The Mobile Training Management to Improve The Quality Results Training - Anak Agung Ngurah Ade Dwi Putra Yuda; Bambang Suratman; Yatim Riyanto (IJORER : International Journal of Recent Educational Research, 2021)
The success of the training can be seen from how the activation process takes place. One of them is by designing an innovative training model. This research aims to analyze results validation of the mobile training management model. This research uses descriptive quantitative analysis in determining the level of validation of research instruments. This research method uses descriptive quantitative research to assess the level of validation of the research instrument. The sample of this research is the participants of basic level seafaring training at the Surabaya Shipping Polytechnic, the Director of the Surabaya Shipping Polytechnic, and local government employees related to mobile training activities. The research was analyzed based on results validation of the training and education management experts. The results reserach show that the mobile training model instrument is declared valid. Results of expert assessment from training management and managing education are categorized as good. This shows that the mobile training development model in improving the quality of education and training is worthy of further research.